Occurrence of PPCPs in a Brazilian water reservoir and their removal efficiency by ecological filtration - Pompei, Caroline Moço Erba; Campos, Luiza Cintra; da Silva, Bianca Ferreira [UNESP]; Fogo, José Carlos; Vieira, Eny Maria (Elsevier, 2019)
The presence of PPCPs (Pharmaceuticals and Personal Care Products) in water sources and drinking water has concerned researchers in recent times. This study was carried out to evaluate the occurrence of 6 PPCPs (namely paracetamol, diclofenac, naproxen, ibuprofen, benzophenone-3 and methylparaben) in the Lobo reservoir, their degradation products, and how efficiently they were removed by 22 ecological filters, considering individual and mixture of compounds. There were 3 spiking events of PPCPs (2 μg L−1) in the ecological filter influents conducted with a lag period of 15 days between spikes. Water samples were collected from the influent and effluent of the filters at 3, 6 and 24 h after each spiking event. All target PPCPs were identified in the Lobo reservoir water in the range of μg L−1. The personal care products were detected with 100% frequency in the samples, and in higher concentrations compared to the pharmaceuticals. Degradation products of diclofenac and benzophenone-3 were identified in the water samples. Results of this investigation show that ecological filtration was an effective process (70–99%) to remove 2 μg L−1 of the selected PPCPs, and demonstrated that the filters were resilient to individual compounds and to their mixtures.
Keywords: Degradation products; Drinking water treatment; Ecological filtration; Removal of PPCPs